2018
DOI: 10.1192/bjp.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric hospitalisation and the risk of suicide

Abstract: SummaryThe association between current or recent psychiatric hospitalisation and increased suicide risk is well described. This relationship is generally assumed to be due to the selection of people at increased risk of suicide for psychiatric admission and subsequent failure of protection from suicide once admitted. Here, Matthew Large and Nav Kapur debate whether or not admission to hospital also selects for vulnerability to certain harmful aspects of hospitalisation and whether the increased rate of suicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 29 publications
3
18
0
1
Order By: Relevance
“…These findings suggest that the perception that psychiatric hospitalization was coerced serves as an indicator of somewhat increased risk that patients will make a suicide attempt after discharge. Previous studies have noted that some patients may feel violated, disrespected, humiliated, or dehumanized by the experience of coercion (Newton‐Howes & Mullen, ; Svindseth, Nøttestad, & Dahl, ; Large & Kapur, ).several studies have observed that perceived coercion is inversely associated with the quality of the therapeutic relationship or with treatment satisfaction (Katsakou et al, ; Sheehan & Burns, ; Strauss et al, ). Although there was no association between perceived coercion and treatment involvement in our sample, participation in treatment is not synonymous with a therapeutic alliance.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the perception that psychiatric hospitalization was coerced serves as an indicator of somewhat increased risk that patients will make a suicide attempt after discharge. Previous studies have noted that some patients may feel violated, disrespected, humiliated, or dehumanized by the experience of coercion (Newton‐Howes & Mullen, ; Svindseth, Nøttestad, & Dahl, ; Large & Kapur, ).several studies have observed that perceived coercion is inversely associated with the quality of the therapeutic relationship or with treatment satisfaction (Katsakou et al, ; Sheehan & Burns, ; Strauss et al, ). Although there was no association between perceived coercion and treatment involvement in our sample, participation in treatment is not synonymous with a therapeutic alliance.…”
Section: Discussionmentioning
confidence: 99%
“…Or it might be that some patients are helped and others hurt by hospitalization after an SRB. If the latter is the case, as many experts believe it is, careful weighing of risks and benefits is needed to determine which patients are likely to be helped and which ones harmed by hospitalization [120]. No guidance exists currently on how this weighing should be done.…”
Section: The Need For Individualized Treatment Rulesmentioning
confidence: 99%
“…Although theorizing exists about the patients most likely to be helped and those most likely to be hurt by hospitalization (129), little empirical research exists on these hypotheses (90). We are attempting to develop an ITR to provide guidance in making this decision in the immediate aftermath of an outpatient suicide attempt.…”
Section: Precision Treatmentmentioning
confidence: 99%